Back to the roots: Ancestral origin and mutual fund manager portfolio choice - Manuel Ammann; Alexander Elmar Cochardt; Simon Straumann; Florian Weigert (University of Cologne, Centre for Financial Research (CFR), 2022)
We exploit variation in the ancestries of U.S. equity mutual fund managers to show that ancestry affects portfolio decisions. Controlling for fund firm location, we find that funds overweight stocks from their managers' ancestral home countries in their non-U.S. portfolio by 132 bps or 20.34% compared with their peers. Similarly, funds overweight industries that are comparatively large in their manager's ancestral home countries. Stocks linked to managers' ancestry do not outperform stocks in the same countries and industries but held by managers of other ancestries. This supports the notion that ancestry-linked investments are not informed but due to familiarity.
Keywords: G11; G41; 330; Culture; Home Bias; Mutual Funds; Portfolio Choice; Fund Managers